The Games for Older Adults Active Life (GOAL) Project for People With Mild Cognitive Impairment and Vascular Cognitive Impairment: A Study Protocol for a Randomized Controlled Trial - Fabbri, Laura; Mosca, Irene Eleonora; Gerli, Filippo; Martini, Leonardo; Pancani, Silvia; Lucidi, Giulia; Savazzi, Federica; Baglio, Francesca; Vannetti, Federica; Macchi, Claudio; , The GOAL Working Group; Sorbi, Sandro; et al. (Frontiers in Neurology, 2019)
Background: People living with Mild Cognitive Impairment (MCI) and Vascular Cognitive Impairment (VCI) are persons who do not fulfil a diagnosis of dementia, but who have a high risk of progressing to a dementia disorder. The most recent guidelines to counteract cognitive decline in MCI/VCI subjects suggest a multidimensional and multi-domain interventions combining cognitive, physical and social activities. The purpose of this study is to test an innovative service that provides a multi-dimensional tele-rehabilitation program through an user-friendly web application. The latter has been developed through a participatory design involving MCI specialists, patients and their caregivers. Particularly, the proposed tele-rehabilitation program includes cognitive, physical and caregiver-supported social activities. The goal is to promote and preserve an active life style and counteract cognitive decline in people living with MCI/VCI. Methods: The study is a randomized controlled trial. Sixty subjects will be randomly assigned to the experimental group, who will receive the tele-rehabilitation program, or the control group, who will not receive any treatment. The trial protocol comprises three steps of assessment for the experimental group: at the baseline (T_0), after tele-rehabilitation program (T_1) and at follow-up after 12-months (T_2). Differently, the control group will be assessed twice: at the baseline and at 12-months follow-up. Both the experimental and the control group will be assessed with a multidimensional evaluation battery, including cognitive functioning, behavioral, functional and quality of life measures. The tele-rehabilitation program lasts 8 weeks and includes cognitive exercises 3 days a week, physical activities 2 days a week, and social activities once a week. In addition, group will be given an actigraph (GENEActiv, Activisinghts Ltd., Cambridgshire, UK) to track physical and sleep activity. Discussion: Results of this study will inform on the efficacy of the proposed tele-rehabilitation to prevent or delay further cognitive decline in MCI/VCI subjects. The expected outcome is to counteract cognitive decline and improve both physical functioning and quality of life. Ethics and dissemination: The study is approved by the Local Ethics Committee and registered in https://clinicaltrials.gov (NCT03383549). Dissemination will include submission to a peer-reviewed journal, patients and healthcare magazines and congress presentations.